2017
DOI: 10.4999/uhod.172036
|View full text |Cite
|
Sign up to set email alerts
|

Which One is The Better Radiotherapy Technique for Patients with Thoracic Esophageal Tumors, IMRT or VMAT?

Abstract: Comparison of IMRT and VMAT techniques in thoracic esophageal tumors. IMRT and VMAT plans were created for a total of 10 thorax-located esophagus patients. All plans were compared in terms of HI and CI for PTV; V 5 , V 10 , V 20 and mean lung dose parameters for total lung; V 30 , V 40 and mean heart dose for the heart; and the Dmax for the medulla spinalis. IMRT and VMAT techniques yielded similar results with respect to HI and CI values (p> 0.05). Median mean lung dose was found to be lower in VMAT (11.77 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…As shown in Table 2 in our study, PTV coverage was achieved as the best in IMAT plan with CI (1.186) and HI (0.056) values. Karaoguz et al in their IMRT and IMAT plans, they found the best values of CI and HI in the IMAT plan as in our study [13]. In addition, in our study Dmax, Dmin, Dmean, D1%, D5% doses for PTV were found as lowest value in IMRT.…”
Section: Conclusion and Commentsupporting
confidence: 76%
“…As shown in Table 2 in our study, PTV coverage was achieved as the best in IMAT plan with CI (1.186) and HI (0.056) values. Karaoguz et al in their IMRT and IMAT plans, they found the best values of CI and HI in the IMAT plan as in our study [13]. In addition, in our study Dmax, Dmin, Dmean, D1%, D5% doses for PTV were found as lowest value in IMRT.…”
Section: Conclusion and Commentsupporting
confidence: 76%